The benthic and epiphytic marine dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands, an updated checklist from 2018 to 2024 - Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; Sarah C. Finch; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
A checklist collating records of New Zealand’s benthic and epiphytic dinoflagellate species was published on‐line in 2018 [Rhodes L, Smith KF. 2019. A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. N Z J Mar Freshw Res. 53:258–277. doi: 10.1080/00288330.2018.1492425 ]. Over the last six years, seventeen species from nine genera (three newly reported genera) have been documented, including sand‐dwelling species. Isolation and identification of species using traditional microscopic techniques combined with analysis of DNA sequencing data has been supplemented by high‐throughput sequencing techniques (i.e. metabarcoding). Toxin data, based on liquid chromatography mass spectrometry (LC‐MS/MS), and toxicity of isolates are included where applicable. Forty‐two benthic and epiphytic dinoflagellate genera, including genera having benthic life stages, have now been recorded in Aotearoa New Zealand coastal waters including Rangitāhua Kermadec Islands (new record genera in bold): Adenoides , Alexandrium , Amphidinium , Archaeperidinium , Azadinium , Biecheleria , Blastodinium , Bysmatrum , Cachonina , Coolia , Crypthecodinium , Cryptoperidiniopsis , Dinophysis , Durinskia , Ensiculifera , Fukuyoa , Fragilidium , Gambierdiscus , Gonyaulax , Gymnodinium , Gyrodinium , Heterocapsa , Karenia , Karlodinium , Kryptoperidinium , Lepidodinium , Ostreopsis , Pelagodinium , Pentapharsodinium , Pfiesteria , Polarella , Prorocentrum , Protodinium , Protoperidinium , Pseudadenoides , Pseudopfiesteria , Scrippsiella , Symbiodinium , Thecadinium , Togula , Vulcanodinium and Woloszynskia.